Study of endometrial and cervical histopathology in adenomyosis - Matangi, Anandakumari; Manukonda, Alpha; Bommiti, Abhizna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hysterectomy is the most common gynaecological surgery performed in the perimenopausal and post-menopausal women all over the world. One of the most common cause of AUB is Adenomyosis based on histopathological evidence and the ultimate mainstay stay of treatment is hysterectomy in those patients not responding to medical therapy. Endocervical and Endometrial histopathology in adenomyosis are studied in this study. Objective of this study was to analyses various histopathological changes of endometrium and cervix in hysterectomy specimens showing features of adenomyosis. Methods: This is a retrospective study conducted at Government Victoria Hospital for Women and Children, Visakhapatnam, Andhra Medical College for a period of one year from January 2019 to December 2019.100 cases with histopathology reports of hysterectomy specimens showing changes suggestive of adenomyosis were studied for 1 year. Those cases which showed features of adenomyosis were taken and the preoperative details and procedures done on the patient were retrieved and endometrial and cervical biopsy, Pap Smear changes of these patients were studied. Results: Out of 100 cases, 37 members (majority) showed features of atrophic endometrium, 69 members (majority) showed features of chronic cervicitis, about 58 members (majority) showed inflammatory changes in Pap Smear. In the 100 cases, 75 cases are in perimenopausal age group i.e., 40-50 years, 80 of them are multiparous women, 85 members had mild to moderate degree of anaemia while only about 15 members had severe anemia. Adenomyosis was found to be the leading cause of AUB. Conclusions: Adenomyosis is one the leading causes of AUB and hence also an important cause of hysterectomy in those with failed medical therapy. Histopathological changes of endometrium and cervix are analyzed from D and C and Pap Smear reports of patients whose specimens are confirmed to be having adenomyosis.